Analysis and Design of Village Management Information Systems (VMIS) based on MVC and E-Government in Indonesia - Halim Maulana; Al-Khowarizmi Al-Khowarizmi; Edy Rahman Syahputra; Mhd. Basri (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
E-Government is the government's program and commitment in the effort to develop electronic-based governance and transforms to facilitate the activities of society and business to the knowledge-based society. E-Governmet can be said to be a system that contains collections of modules that can be integrated with others. Considering the many module components in the e-government authors in this study limits only to population modules such as service and management of population data, KK data, data on population mutations such as population (moving, coming, born, dead) built using the Model View method Web-based and online controller. As well as how to simplify the management of the letter, in addition to facilitate the search population data and information about the development of villagers in each village in real time with terintegerasinya data to each village in addition to facilitate and accelerate the service request and manufacture reporting. So with the existence of this system the kecamatan easier to see the development of data of the population of each village and with this system the kecamatan and village easier to manage the data letter and can facilitate in sending mail to each village. With this research, it is expected Sub-district offices can provide improvement of information service and also data processing of its population.